EVALUASI KINERJA TEKNOLOGI INFORMASI (TI) BERBASIS IT BALANCE SCORE CARD (STUDI KASUS UNIVERSITAS BALIKPAPAN) - anwar fattah (Lembaga Penelitian Universitas Balikpapan, 2017)
In this research is where to find out the performance of information technology IT at the University of Balikpapan. Measurement using a four (4) in the framework of the Balance Score Card IT Business/Customer Contribution, User Orientation, Operational Excellence and Future Orientation. The research results obtained that the aspects of Future Orientation (FO) effect on performance of IT on University of Balikpapan, Excellent Operational effect on the performance of IT on University of Balikpapan, User Orientation has no effect against The performance of IT on University of Balikpapan And Customer Contribution does not affect the performance of IT on University of Balikpapan